Leitura e cibercultura: navegando em oceanos pedagógicos ou por uma educação popular nunca de antes navegada - Oliveira, Dimas Lucena de (2006)
The cyber culture can to be a pedagogic space that allows tools for the construction of new reading practices, valuing creativity, affection, interaction and group growing in the perspective of reader s formation. It was built some reflexions over the importance and the meaning of Reading in the educational process, with a critical comprehension of the reading's pedagogical processes and the systematic brought up by technological evolution and the consequent appearance of the digital reading, that is, the tools available on the cyber culture. It has made an analysis about the relationship of the Reading and the School, outstandingly fundamented in the thoughts of Freire over reading and on Levy's about cyber culture. It was intended to demonstrate how the manipulation of information and communication technologies can be an important tool to increase the motivation and dynamics of the reading's process development, hence establishing, according to the pedagogical conception that makes it's utilization viable, an efficient and contemporary relationship. For this matter, methodologically inspired in Pichon-Rivière, operative groups were built, where it was developed pedagogical activities of reading, analysis and interpretation of texts. As a result it was attested the viability of the genesis proposition of this research, that is, through the elements of the cyber culture it is possible to create easening conditions to the formation of selfmotivated and critical readers, over all capable of analyzing and interpreting texts.